Why Does Parenting Style Matter on Student’s Confidence at Buddhist Sunday School? - Sutiyono; Suryanadi, Juni; Sutawan , Komang; Marwintaria, Vike Aprilianin; Astika , Ria (Journal of Education, Religious, and Instructions (JoERI), 2023)
Abstract Research with approach quantitative this study aims to investigate the effect of parenting style on the self-confidence of Buddhist Sunday School students at Amurwa Bumi Graha—pattern fostering can role important in forming confidence in self-individual, incl in the context of student self-confidence. Data were collected from 108 respondents using relevant instruments. Regression analysis was conducted to see the relationship between the independent variable, parenting style, and the dependent variable, student self-confidence. The test results show that the regression model has good quality, with a coefficient of determination (R Square) of 0.916. The results of the coefficient test show that parenting style has a significant and positive influence on students' self-confidence. In conclusion, this study supports the hypothesis that parenting style influences the self-confidence of Buddhist Sunday School students.